Basic Engine Training Of Gasoline Injection System Pada Guru Produktif SMK Keahlian Teknik Kendaraan Ringan - Farid Majedi; Achmad Aminudin; Muhammad Taali; Nanang Romandoni (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The development of technology in the automotive sector, especially four-wheeled vehicles is increasing. This is shown by the use of Electronic Fuel Injection (EFI) technology for the fuel intake system. Therefore, teachers must continue to upgrade their skills and expertise in order to improve the quality of graduates. SMK Teknik Bakti Persada is a school that has one of the light vehicle engineering expertise programs. Judging from the tools and machines that are in the workshop, the average is a machine with EFI technology. There needs to be an effort to improve teacher competence related to the gasoline injection system. Gasoline injection system training is a community service program that aims to improve the competence of productive teachers at SMK Teknik Bakti Persada. The training method applied is theory and practice which is carried out for 4 days. The results showed that the trainees were able to disassemble the starter motor, alternator, tune up the EFI engine, and use a scanner to stream engine data. Improving the skills of vocational school teachers is expected to have an impact on the quality of graduates who are quickly absorbed in the industrial world.